Confederate general of the West : Henry Hopkins Sibley - Thompson, Jerry D. (Texas A & M University Press, 1996)
Had Henry Hopkins Sibley and his troops succeeded in taking New Mexico, author Jerry Thompson argues, "the entire history of the Southern Confederacy might have been radically altered." In Confederate General of the West, Thompson portrays the life and career of a soldier whose character flaws and leadership weaknesses stood in stark contrast to his sometime military successes and mechanical ingenuity. Civil War scholars, students, and enthusiasts will welcome this new paperback edition of Sibley's biography. As the Utah Historical Quarterly noted after the book first appeared in 1987, Jerry Thompson's scholarship "has provided us with a view of nineteenth-century American military life that rarely surfaces - a comprehensive picture of the mediocre, inept officer who, when thrust into positions of great pressure and responsibility, unwittingly produces great carnage.... Perhaps the greatest value of the book is the extent to which it illustrates the impact of frontier isolation ... on the contentious behavior of the army's officer corps during the antebellum period."